2018
DOI: 10.1158/1078-0432.ccr-17-3384
|View full text |Cite
|
Sign up to set email alerts
|

Dual MAPK Inhibition Is an Effective Therapeutic Strategy for a Subset of Class II BRAF Mutant Melanomas

Abstract: Dual MAPK pathway inhibition (dMAPKi) with BRAF and MEK inhibitors improves survival in BRAF V600E/K mutant melanoma, but the efficacy of dMAPKi in non-V600 BRAF mutant tumors is poorly understood. We sought to characterize the responsiveness of class II (enhanced kinase activity, dimerization dependent) BRAF mutant melanoma to dMAPKi. Tumors from patients with BRAF wild-type (WT), V600E (class I), and L597S (class II) metastatic melanoma were used to generate patient-derived xenografts (PDX). We assembled a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
60
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 48 publications
3
60
1
Order By: Relevance
“…In concordance with these data, we found that patients with advanced melanoma with class 2 or 3 BRAF mutations (and/or NRAS mutations) also have shorter survival compared with those with class 1 BRAF mutations (3). We have reported that subsets of class 2 BRAF-mutant melanomas are sensitive to MAPK inhibition (3). As such, we expect that class 2 BRAF-mutant NSCLC may also be sensitive to a similar therapeutic approach.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…In concordance with these data, we found that patients with advanced melanoma with class 2 or 3 BRAF mutations (and/or NRAS mutations) also have shorter survival compared with those with class 1 BRAF mutations (3). We have reported that subsets of class 2 BRAF-mutant melanomas are sensitive to MAPK inhibition (3). As such, we expect that class 2 BRAF-mutant NSCLC may also be sensitive to a similar therapeutic approach.…”
supporting
confidence: 85%
“…Dagogo-Jack and colleagues found that patients with class 2 or 3 BRAF mutations have shorter survival times than patients with class 1 BRAF mutations. In concordance with these data, we found that patients with advanced melanoma with class 2 or 3 BRAF mutations (and/or NRAS mutations) also have shorter survival compared with those with class 1 BRAF mutations (3). We have reported that subsets of class 2 BRAF-mutant melanomas are sensitive to MAPK inhibition (3).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…However, precision medicine efforts to date have largely focused on the V600 subset where repurposing melanoma drugs has led to significant and durable responses (19,20). Preclinical studies suggest that classifying BRAF mutants by underlying kinase activity and RAF signaling mechanism may be more informative than grouping tumors according to V600 status (14,16,21). These preclinical observations are supported by case reports and small series demonstrating distinct activity of available BRAF inhibitors in lung cancers with class I, II, or III mutations (19,22,23).…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, BRAF inhibitors facilitate dimerization of wild type RAF proteins, and actually paradoxically activate the MAPK signaling pathway; this was particularly demonstrated in the promotion of cutaneous squamous cell carcinomas in patients receiving BRAF inhibitors. However, the addition of a MEK inhibitor mitigates these concerns, and even some patients without BRAF V600 mutations may derive benefits from BRAF/MEK inhibition .…”
Section: Discussionmentioning
confidence: 99%